About theaters and methods (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text discusses some procedures used to read the differential theatricalities to which they respond. It mentions genetic criticism, theatrical semiology, instruments linked to the post-dramatic and performative theatre and the ethnographic method, associated with specific scenic occurrences.
Keywords: contemporary theater; performance; methodological procedures